LEGAL PROBLEMS AND OBSTACLES CONCERNING ON THE ENVIRONMENTAL IMPRACT ASSESSMENT REPORT OF MENDACIOUS - Sukjit, Sujira (Academic Journal Phranakhon Rajabhat University, 2021)
The objectives of this thesis were to investigate the background and significance of the false environmental impact analysis problem, to study legal measures related to wrong environmental impact analysis problem, to research and analyze the nature of the offense and the status of the victim in the preparation of a false environmental impact report and to obtain a summary and recommendations for amending the Enhancement and Conservation of National Environmental Quality Act, B.E. 2535 (1992) to apply the research results for further analysis to identify legal measures to amend the law appropriately. This study was documentary research, which was conducted by exploring related laws. The results of this study indicated that in the preparation of the environmental impact reports in Thailand, the Enhancement and Conservation of National Environmental Quality Act, B.E. 2535 (1992) is a primary law that stipulated only penalties for those who do not submit the report, but did not impose any legal measures that impose penalties for those preparing a false environmental impact report and provisions on the status of a victim from the said preparation of a false environmental impact report by studying the legal measures related to falsehoods under the Criminal Code and the status of the victim under the Criminal Procedure Code to implement punishment measures. Therefore, the study suggests that the penalties for those making false environmental impact reports should be amended based on the penalties under the Criminal Code, the Enhancement and Conservation of National Environmental Quality Act, B.E. 2535 (1992), and the Ministerial Regulations are included in the Enhancement and Conservation of National Environmental Quality Act, B.E. 2535 (1992) in order not to apply several laws to punish those who have committed offenses under the Enhancement and Conservation of National Environmental Quality Act, B.E. 2535 (1992), including the damage caused by the preparation of false environmental impact reports in the Enhancement and Conservation of National Environmental Quality Act, B.E. 2535 (1992).